2006
DOI: 10.1191/0269216306pf858oa
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial protective effects of nicorandil, an opener of potassium channels on senile rat heart

Abstract: The purpose of this study was to investigate the cardioprotective effects of nicorandil, an opener of potassium channels, on senile rat hearts from ischemic reperfusion injury. A modified working model of isolated perfused hearts of senile rats was used. After isolation, the hearts underwent 60 min of global hypothermic ischemia treatment, followed by 30 min of reperfusion. These hearts were distributed into three groups, each receiving different cardioplegic solutions: (1) St. Thomas' solution (Group S), (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Indeed, additional investigations are clearly required to make an inventory of the multiples mechanisms whereby endurance training can first protect aging of the heart and second limit its vulnerability to IR and especially: ionichomeostasis (Tani et al, 1999;Besse et al, 2004;Liu et al, 2006b), endothelin production (Besse et al, 2001), Bax/Bcl-2 ratio and apoptosis (Liu et al, 2002) or mitochondrial defects (Lesnefsky et al, 2006). Active tension 6.9 ± 0.3 7.4 ± 0.5 (g.g -1 heart weight)…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, additional investigations are clearly required to make an inventory of the multiples mechanisms whereby endurance training can first protect aging of the heart and second limit its vulnerability to IR and especially: ionichomeostasis (Tani et al, 1999;Besse et al, 2004;Liu et al, 2006b), endothelin production (Besse et al, 2001), Bax/Bcl-2 ratio and apoptosis (Liu et al, 2002) or mitochondrial defects (Lesnefsky et al, 2006). Active tension 6.9 ± 0.3 7.4 ± 0.5 (g.g -1 heart weight)…”
Section: Discussionmentioning
confidence: 99%
“…Many of the heart studies have compared one preservation solution with another,26,29–33,35,3944 and with or without additives, such as channel activators or blockers,1,11,4549 exchange inhibitors,5052 anesthetics,2,9,49 nitric oxide (NO) donors,53 perfluorocarbons54 or BDM 1,30,55. For example, Celsior solution preserved function better than ViaSpan in several studies,44,56 whereas others found that ViaSpan was better than Celsior 29,30.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, K + channel openers have been added to cardioplegic solutions to determine whether this enhances cardioprotection in experimental models (Table ). The addition of K ATP channel openers (pinacidil, diazoxide, nicorandil) to crystalloid cardioplegia enhances the recovery of contractile function in reperfusion in Langendorff‐perfused rabbit and rat hearts . K ATP channel openers also reduce infarct size, ultrastructural damage and mitochondrial damage, although whether they reduce release of cardiac enzymes is controversial .…”
Section: Pharmacologic Agents In Cardioplegia In Pre‐clinical Models mentioning
confidence: 99%
“…The addition of K ATP channel openers (pinacidil, diazoxide, nicorandil) to crystalloid cardioplegia enhances the recovery of contractile function in reperfusion in Langendorff‐perfused rabbit and rat hearts . K ATP channel openers also reduce infarct size, ultrastructural damage and mitochondrial damage, although whether they reduce release of cardiac enzymes is controversial . Diazoxide cardioplegia also improves contractile function and reduces infarct size in a rabbit cardiopulmonary bypass model .…”
Section: Pharmacologic Agents In Cardioplegia In Pre‐clinical Models mentioning
confidence: 99%
See 1 more Smart Citation